2012
DOI: 10.5562/cca1915
|View full text |Cite
|
Sign up to set email alerts
|

Crystal Structure of Citrobacter freundii Asp214Ala Tyrosine Phenollyase Reveals that Asp214 is Critical for Maintaining a Strain in the Internal Aldimine

Abstract: Abstract. Tyrosine phenol-lyase (TPL) is a pyridoxal-5′-phosphate (PLP) dependent enzyme which catalyzes β-elimination of L-tyrosine. In the holoenzyme the protonated pyridinium N1 atom of the PLP cofactor is hydrogen-bonded to the side chain of Asp214. Here we report the X-ray structure of C. freundii D214A TPL determined at 1.9 Å resolution. Comparison with the structure of the wild-type TPL shows that the D214A replacement induced significant conformational reorganization in the active site leading to its p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…This aspartate is necessary for TPL activity, since D214A TPL has no activity with L-tyrosine or 3-F-L-tyrosine [22]. The X-ray crystal structure of mutant D214A TPL revealed that the interaction of Asp-214 with the pyridine ring nitrogen supports C a -H-acidity of the external aldimine and the strained conformation of the internal aldimine [23]. It was proposed that in the aminotransferase superfamily the strictly conservative aspartate residue provides both the electron sink properties of the cofactor and an acceleration of the transaldimination stage.…”
Section: Structure Of Til and Tplmentioning
confidence: 96%
“…This aspartate is necessary for TPL activity, since D214A TPL has no activity with L-tyrosine or 3-F-L-tyrosine [22]. The X-ray crystal structure of mutant D214A TPL revealed that the interaction of Asp-214 with the pyridine ring nitrogen supports C a -H-acidity of the external aldimine and the strained conformation of the internal aldimine [23]. It was proposed that in the aminotransferase superfamily the strictly conservative aspartate residue provides both the electron sink properties of the cofactor and an acceleration of the transaldimination stage.…”
Section: Structure Of Til and Tplmentioning
confidence: 96%
“…The site-directed mutagenesis of Asp214 to Ala led to deprotonation of the pyridine ring N, the reduced reaction activity, one assumed relaxed geometry and the increased stability of the internal aldimine. It was proposed that this observed stabilization of the ground state in D214A variant might reduce the rate of the external aldimine formation, while Asp214 in wild-type enzyme might maintain the strained state of the internal aldimine, which likely led to the acceleration of transaldimination (Milić et al, 2012 ). The Asp residue is usually conserved, but in some enzymes, this residue is replaced by a Glu, which can interact with PLP pyridine ring N in the same manner (forming salt bridge) in fold type I and IV enzymes.…”
Section: Mechanism Of Reaction Specificitymentioning
confidence: 99%